Highly dispersed buckybowls as model carbocatalysts for C–H bond activation1. Issue 16 (28th April 2015) - Soykal, I. Ilgaz; Wang, Hui; Park, Jewook; Li, An-Ping; Liang, Chengdu; Schwartz, Viviane
<x xml:space="preserve">Abstract</x> Fullerene fragments function as highly active and selective carbon catalysts for C–H bond activation.